Double-spiral: a bioinspired pre-programmable compliant joint with multiple degrees of freedom. Issue 198 (11th January 2023) - Jafarpour, Mohsen; Gorb, Stanislav; Rajabi, Hamed
Abstract : Geometry and material are two key factors that determine the functionality of mechanical elements under a specific boundary condition. Optimum combinations of these factors fulfil desired mechanical behaviour. By exploring biological systems, we find widespread spiral-shaped mechanical elements with various combinations of geometries and material properties functioning under different boundary conditions and load cases. Although these spirals work towards a wide range of goals, some of them are used as nature's solution to compactify highly extensible prolonged structures. Characterizing the principles underlying the functionality of these structures, here we profited from the coiling–uncoiling behaviour and easy adjustability of logarithmic spirals to design a pre-programmable compliant joint. Using the finite-element method, we developed a simple model of the joint and investigated the influence of design variables on its geometry and mechanical behaviour. Our results show that the design variables give us a great possibility to tune the response of the joint and reach a high level of passive control on its behaviour. Using 3D printing and mechanical testing, we replicated the numerical simulations and illustrated the application of the joint in practice. The simplicity, pre-programmability and predictable response of our double-spiral design suggest that it provides an efficient solution for a wide range of engineering applications, such as articulated robotic systems and modular metamaterials.